Produção Científica dos Cursos de Licenciatura em Computação no Brasil - Jonathan Rosa Moreira; Jefferson Bruno Pereira Ribeiro; Cláudia Pinheiro Nascimento; Maristela Terto de Holanda; Geilson Dos Santos Sá (Brazilian Journal of Information Science: research trends, 2026)
This study analyzes the scientific production represented by undergraduate final papers from Computer Science Teacher Education programs at Brazilian public institutions, submitted between 2015 and 2025 and retrieved from institutional repositories, in order to identify temporal, institutional, thematic, and authorship patterns as well as aspects related to availability. A quantitative, documentary, and descriptive approach was adopted, using bibliometric procedures. The corpus comprises 1,023 final papers retrieved from 17 institutions; the authorship dataset contains 1,244 author records associated with 1,021 of these papers. The educational area accounts for 841 papers (82.2%) and the technical area for 182 (17.8%). Differences among institutions were also observed in the volume of retrieved documents, as was heterogeneity in repository organization. Because data collection depended on the availability and retrieval mechanisms of each system, the results describe the corpus identified up to March 28, 2026 and should not be interpreted as the totality of final papers produced by the programs.